Neuronal tracing of oral nerves in a velvet worm—Implications for the evolution of the ecdysozoan brain - Martin, Christine; Mayer, Georg (Frontiers in Neuroanatomy, 2014)
As one of the closest relatives of arthropods, Onychophora plays an important role in understanding the evolution of arthropod body plans. Currently there is controversy surrounding the evolution of the brain among the ecdysozoan clades, which shows a collar-shaped, circumoral organisation in cycloneuralians but a ganglionic architecture in panarthropods. Based on the innervation pattern of lip papillae surrounding the mouth, the onychophoran brain has been interpreted as a circumoral ring, suggesting that this organisation is an ancestral feature of Ecdysozoa. However, this interpretation is inconsistent with other published data. To explore the evolutionary origin of the onychophoran mouth and to shed light on the evolution of the ecdysozoan brains, we analysed the innervation pattern and morphogenesis of the oral lip papillae in the onychophoran Euperipatoides rowelli using DNA labelling, immunocytochemistry and neuronal tracing techniques. Our morphogenetic data revealed that the seven paired and one unpaired oral lip papillae arise from three anterior-most body segments. Retrograde fills show that only the first and the third nerves supplying the lip papillae are associated with cell bodies within the brain, whereas the second nerve exclusively receives fibres from somata of peripheral neurons located in the lip papillae. According to our anterograde fills and immunocytochemical data, the first nerve supplies the anterior-most pair of lip papillae, whereas the second and the third nerves are associated with the second to fifth and second to eighth lip papillae, respectively. These data suggest that the lip papillae of E. rowelli are mainly innervated by the proto- and deutocerebrum, whereas there are only a few additional cell bodies situated posterior to the brain. According to these findings, the overall innervation pattern of the oral lip papillae in E. rowelli is incompatible with the interpretation of the onychophoran brain as a modified circumoral ring.